A low-energy-consumption and low-cost quartz fiber preparation method
Patent Information
- Application Number
- CN202610697877.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-20
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-05-20
AI Technical Summary
(1)棒拉丝法是将高纯石英原料熔融拉制成石英棒,再用氢氧焰等高温火焰加热棒端,同时以恒定速度向下拉制,形成连续纤维,其工艺控制相对成熟,避开了合金漏板等配套设备的要求,产品质量稳定,主流工业化生产方法,但该工艺经过2次熔融,能耗高,且属于单拉丝工艺,成本高
本发明通过先制备熔化温度相对较低的石英先驱体,再进行多孔漏板批量拉丝的方式制备石英先驱体纤维,最终通过酸洗与烧结得到石英纤维,无需2000℃以上的熔融温度,降低了高温工艺带来的高能耗与设备要求,且能够一次成型多束纤维,生产效率高、成本低。
Abstract
Description
Technical Field
[0001] This invention relates to the preparation of mineral fibers, and more particularly to a method for preparing quartz fibers with low energy consumption and low cost. Background Technology
[0002] Quartz fiber, with its high temperature resistance, low dielectric loss, high strength and modulus, and thermal shock resistance, has become an indispensable strategic key material in high-end fields such as aerospace and electronic communications. Currently, there are three main manufacturing processes for quartz fiber: rod drawing, direct melt drawing, and sol-gel method, with the specific technical routes as follows: (1) The rod drawing method involves melting high-purity quartz raw materials and drawing them into quartz rods. The rod ends are then heated with high-temperature flames such as hydrogen-oxygen flames and drawn downwards at a constant speed to form continuous fibers. The process control is relatively mature, avoiding the requirements of supporting equipment such as alloy spinnerets. The product quality is stable and it is the mainstream industrial production method. However, this process involves two meltings, resulting in high energy consumption. It is also a single drawing process with high cost.
[0003] (2) Direct melt drawing method, such as the quartz glass fiber cloth and its preparation method disclosed in patent application No. 202511331674.4, involves melting high-purity quartz sand at high temperature to form quartz glass liquid, drawing it into continuous quartz fiber bundles through an alloy stencil, and then acid washing and low-temperature pre-baking treatment of the fiber bundles; subsequently, drying and sintering are carried out to form quartz glass fibers. This is an ultra-high temperature process, and the drawing process needs to be carried out at extremely high temperatures of 1800-2200℃. It has stringent requirements for equipment such as high-temperature furnaces, crucibles, and alloy stencils, and has high energy consumption.
[0004] (3) The sol-gel method uses high-purity organosilicon compounds as precursors. A sol is obtained through hydrolysis and condensation reactions. By controlling conditions such as pH and temperature, the sol particles gradually crosslink to form a three-dimensional network, lose their fluidity, and become a gel. When the viscosity is suitable, it can be directly spun into gel fibers through a drawing process. Finally, ultra-high purity quartz fibers are obtained through drying and high-temperature sintering. This process has a low temperature, but the preparation process is long, the process control is complex, and the raw materials are expensive, resulting in high production costs.
[0005] Therefore, the equipment or process requirements and production costs for quartz fiber preparation are relatively high, which limits its manufacturing and application to a certain extent. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to provide a method for preparing quartz fibers with low energy consumption and low cost.
[0007] To solve the above-mentioned technical problems, the technical solution of the present invention is as follows: a low-energy-consumption and low-cost method for preparing quartz fibers, the innovation of which is that the preparation method includes: a drawing process, in which quartz sand with added alkaline flux is melted, and the melting temperature of the mixture is controlled below 1650°C by using alkaline flux to obtain molten quartz precursor; then the molten quartz precursor is drawn into quartz precursor fibers through an alloy porous stencil; an acid washing process, in which the quartz precursor fibers are acid washed to remove impurity phases in the quartz precursor fibers; and a sintering process, in which the acid-washed quartz precursor fibers are sintered to obtain quartz fibers with a SiO2 content of more than 99%.
[0008] Preferably, the quartz sand contains SiO2 and Al2O3, with SiO2 accounting for more than 99 wt% of the total quartz sand and Al2O3 accounting for 0.2 to 0.43 wt% of the total quartz sand; and the content of alkaline flux in the mixture of quartz sand and alkaline flux is 15 to 25 wt%.
[0009] Preferably, the content of Al2O3 in the total amount of quartz sand is controlled at 0.33~0.4wt%; and the content of alkaline flux in the mixture of quartz sand and alkaline flux is 18~24wt%.
[0010] Preferably, the alkaline flux is sodium carbonate.
[0011] Specifically, in the pickling process, the pickling solution used for the quartz precursor fibers is hydrochloric acid or sulfuric acid.
[0012] Specifically, the quartz precursor fibers are woven before the pickling process.
[0013] The advantages of this invention are: This invention prepares quartz precursor fibers by first preparing a quartz precursor with a relatively low melting temperature, then using a porous stencil for batch drawing, and finally obtaining quartz fibers through acid washing and sintering. This eliminates the need for a melting temperature above 2000℃, reducing the high energy consumption and equipment requirements of high-temperature processes, and enables the one-time forming of multiple fiber bundles, resulting in high production efficiency and low cost.
[0014] The controlled ratio of alkaline flux to quartz sand ensures metastable phase separation of the molten quartz precursor. The synergistic effect of sodium and aluminum oxides in the quartz sand and alkaline flux, combined with the control of preparation process parameters, enables uniform phase separation. This ensures the separation into two interconnected microstructures at the nanoscale: a high-silica phase and an impurity phase. This allows for complete removal of the impurity phase during the pickling process and facilitates the subsequent cleaning of the pickling solution and dissolved salts in the three-dimensional channel obtained after impurity phase removal. It also avoids large differences in phase separation regions that could affect fiber strength. Detailed Implementation
[0015] This invention relates to a low-energy-consumption and low-cost method for preparing quartz fibers. The method includes: a drawing process in which quartz sand with added alkaline flux is melted, and the melting temperature of the mixture is controlled below 1650°C using the alkaline flux to obtain a molten quartz precursor; and then the molten quartz precursor is drawn into quartz precursor fibers through an alloy porous stencil. The pickling process involves pickling the quartz precursor fibers or the quartz precursor fiber cloth obtained after weaving them to remove the impurity phases in the quartz precursor fibers. In the sintering process, the acid-washed quartz precursor fibers are sintered to obtain quartz fibers with a SiO2 content of over 99%.
[0016] In this invention, the quartz sand contains SiO2 and Al2O3, with SiO2 accounting for more than 99 wt% of the total quartz sand content and Al2O3 content controlled at 0.2-0.4 wt%. The alkaline flux content in the mixture of quartz sand and alkaline flux is 15-25 wt%. More specifically, the alkaline flux is sodium carbonate or sodium oxide. In the pickling process, the pickling solution used for the quartz precursor fibers is hydrochloric acid or sulfuric acid, with the sulfuric acid generally being a dilute sulfuric acid concentration of 10-20 wt%. In the sintering process, the sintering temperature is generally 550-750℃, and the time is approximately 15-40 minutes.
[0017] Example 1
[0018] The preparation method in this embodiment is as follows: The first step is the wire drawing process, in which sodium carbonate is added to the quartz sand as an alkaline flux. The mixture of quartz sand and alkaline flux is melted to obtain molten quartz precursor. The molten quartz precursor is then drawn into quartz precursor fibers through an alloy porous stencil. The diameter of the quartz precursor fibers is 5~8μm.
[0019] The next step is the acid pickling process, which involves acid pickling the quartz precursor fibers to remove impurity phases within them. The acid pickling temperature is controlled at 60±5℃, and the pickling time is 5~24h. In this embodiment, the concentration of dilute sulfuric acid is controlled at 16±1wt%.
[0020] Finally, the sintering process is carried out, in which the acid-washed quartz precursor fibers are sintered to obtain quartz fibers. The sintering temperature is 720℃ and the time is about 30 minutes.
[0021] In this embodiment, the content of SiO2 in the quartz sand accounts for 99.20 wt% of the total quartz sand, the content of Al2O3 accounts for 0.40 wt% of the total quartz sand, and the remainder is impurities.
[0022] In this embodiment, the content of quartz sand accounts for 85 wt% of the total mixture, the content of alkaline flux accounts for 15 wt% of the total mixture, and the melting temperature of the mixture is 1608°C.
[0023] Example 2
[0024] The preparation method of this embodiment is exactly the same as that of Example 1, and the content of SiO2 and Al2O3 in the selected quartz sand is also exactly the same. The difference is that the content of quartz sand in the mixture is 82wt%, the content of alkaline flux is 18wt%, and the melting temperature of the mixture is 1589℃.
[0025] Example 3
[0026] The preparation method of this embodiment is exactly the same as that of Example 1, and the contents of SiO2 and Al2O3 in the selected quartz sand are also exactly the same. The difference is that the content of quartz sand in the mixture is 79wt%, the content of alkaline flux is 21wt%, and the melting temperature of the mixture is 1554℃.
[0027] Example 4
[0028] The preparation method of this embodiment is exactly the same as that of Example 1, and the content of SiO2 and Al2O3 in the selected quartz sand is also exactly the same. The difference is that the content of quartz sand in the mixture is 76wt%, the content of alkaline flux is 24wt%, and the melting temperature of the mixture is 1532℃.
[0029] Example 5
[0030] The preparation method of this embodiment is exactly the same as that of Example 1, and the content of SiO2 and Al2O3 in the selected quartz sand is also exactly the same. The difference is that the content of quartz sand in the mixture is 75wt%, the content of alkaline flux is 25wt%, and the melting temperature of the mixture is 1503℃.
[0031] Comparative Example 1 The preparation method of this embodiment is exactly the same as that of Example 1, and the content of SiO2 and Al2O3 in the selected quartz sand is also exactly the same. The difference is that the content of quartz sand in the mixture is 90wt%, the content of alkaline flux is 10wt%, and the melting temperature of the mixture is 1903℃.
[0032] Comparative Example 2 The preparation method of this embodiment is exactly the same as that of Example 1, and the content of SiO2 and Al2O3 in the selected quartz sand is also exactly the same. The difference is that the content of quartz sand in the mixture is 87wt%, the content of alkaline flux is 13wt%, and the melting temperature of the mixture is 1720℃.
[0033] Comparative Example 3 The preparation method of this embodiment is exactly the same as that of Example 1, and the contents of SiO2 and Al2O3 in the selected quartz sand are also exactly the same. The difference is that the content of quartz sand in the mixture is 74wt%, the content of alkaline flux is 26wt%, and the melting temperature of the mixture is 1498℃.
[0034] Comparative Example 4 The preparation method of this embodiment is exactly the same as that of Example 1, and the content of SiO2 and Al2O3 in the selected quartz sand is also exactly the same. The difference is that the content of quartz sand in the mixture is 73wt%, the content of alkaline flux is 27wt%, and the melting temperature of the mixture is 1437℃.
[0035] Table 1 shows the process parameters for Examples 1-5 and Comparative Examples 1 and 2: Example 1 15 85 99.2 0.4 1608 Example 2 18 82 99.2 0.4 1589 Example 3 21 79 99.2 0.4 1554 Example 4 24 76 99.2 0.4 1532 Example 5 25 75 99.2 0.4 1503 Comparative Example 1 10 90 99.2 0.4 1903 Comparative Example 2 13 87 99.2 0.4 1740 Comparative Example 3 26 74 99.2 0.4 1498 Comparative Example 4 27 73 99.2 0.4 1437 As shown in Table 1 above, the melting temperature gradually decreases with the increase of alkaline flux addition. The melting temperatures of Examples 1-5 and Comparative Examples 3 and 4 do not exceed 1608℃, with Comparative Example 4 having the lowest melting temperature, not exceeding 1440℃. In contrast, Comparative Examples 1 and 2 have higher melting temperatures, reaching over 1740℃, resulting in higher energy consumption required for wire drawing.
[0036] Table 2 compares the SiO2 content of the quartz fibers obtained in Examples 1-5 and Comparative Examples 1 and 2: Comparative Example 1 98.15 99.2 99.21 Comparative Example 2 97.62 99.17 99.19 Example 1 97.21 99.14 99.22 Example 2 97.74 99.21 99.27 Example 3 96.36 99.18 99.17 Example 4 95.42 99.01 99.03 Example 5 93.61 98.82 99.01 Comparative Example 3 92.2 97.13 97.79 Comparative Example 4 89.18 96.04 96.77 As can be seen from Table 2 above, the SiO2 content in the quartz fibers of Comparative Examples 3 and 4 is less than 98 wt%, while the SiO2 content in the quartz fibers of Examples 1-5 and Comparative Examples 1 and 2 is higher, all reaching over 99 wt%, indicating superior technical indicators. Furthermore, in Examples 1-5 and Comparative Examples 1 and 2, the difference in SiO2 content after 12 hours of pickling is not significant compared to that after 24 hours of pickling, except for Example 5 where the difference is 0.16 wt%, the differences are all less than 0.1 wt%. This means that the final SiO2 content in the quartz fibers can be obtained after 12 hours of pickling. However, in Comparative Examples 3 and 4, the difference in SiO2 content after 12 hours of pickling and 24 hours of pickling is much larger, reaching over 0.6 wt%. Therefore, Comparative Examples 3 and 4 require longer or even double the pickling time to increase the SiO2 content of the quartz fibers, resulting in low production efficiency. Even with double the pickling time, the SiO2 content remains low. Furthermore, the SiO2 content of the quartz fiber after pickling for 24 hours in Example 3 was lower than that after pickling for 12 hours, which may be due to measurement error.
[0037] Example 6
[0038] This embodiment describes a method for preparing quartz fiber cloth: In the fiber drawing process, sodium carbonate is added to quartz sand as an alkaline flux. The mixture of quartz sand and alkaline flux is melted to obtain molten quartz precursor. The molten quartz precursor is then drawn into quartz precursor fibers through an alloy porous stencil. The diameter of the quartz precursor fibers is controlled at 5~8μm.
[0039] In the weaving process, the quartz precursor fibers are woven into quartz precursor fiber fabric with a fabric density of 59±2 warp yarns / 25mm and 46±2 weft yarns / 25mm.
[0040] The pickling process involves pickling the quartz precursor fiber fabric to remove impurity phases. The pickling solution is a dilute sulfuric acid solution with a concentration of 16±1wt%, the pickling temperature is controlled at 60±5℃, and the pickling time is 12 hours.
[0041] In the sintering process, the quartz precursor fiber cloth is dried and sintered to obtain electronic-grade quartz fiber cloth. In this embodiment, the sintering temperature is 720℃ and the time is 30 minutes. The unit area mass of the electronic-grade quartz fiber cloth is controlled at 45.1~48.5 g / m². 2 .
[0042] This embodiment uses the same mixture ratio as in Example 2, that is, the content of quartz sand accounts for 82 wt% of the total mixture, and the content of alkaline flux accounts for 18 wt% of the total mixture. However, in the selected quartz sand, the content of SiO2 accounts for 99.20 wt% of the total quartz sand, the content of Al2O3 accounts for 0.20 wt% of the total quartz sand, and the rest are impurities.
[0043] Example 7
[0044] The method for preparing quartz fiber cloth in this embodiment is exactly the same as that in Example 6, and the mixture ratio is also the same. The difference is that the content of SiO2 in the selected quartz sand accounts for 99.2 wt% of the total quartz sand, the content of Al2O3 accounts for 0.33 wt% of the total quartz sand, and the rest are impurities.
[0045] Example 8
[0046] The method for preparing quartz fiber cloth in this embodiment is exactly the same as that in Example 6, and the mixture ratio is also the same. The difference is that the content of SiO2 in the selected quartz sand accounts for 99.2 wt% of the total quartz sand, the content of Al2O3 accounts for 0.40 wt% of the total quartz sand, and the rest are impurities.
[0047] Example 9
[0048] The method for preparing quartz fiber cloth in this embodiment is exactly the same as that in Example 6, and the mixture ratio is also the same. The difference is that the content of SiO2 in the selected quartz sand accounts for 99.2 wt% of the total quartz sand, the content of Al2O3 accounts for 0.43 wt% of the total quartz sand, and the rest are impurities.
[0049] Comparative Example 5 The method for preparing quartz fiber cloth in this embodiment is exactly the same as that in Example 6, and the mixture ratio is also the same. The difference is that the SiO2 content in the selected quartz sand accounts for 99.2 wt% of the total quartz sand, the Al2O3 content accounts for 0.15 wt% of the total quartz sand, and the rest are impurities.
[0050] Comparative Example 6 The method for preparing quartz fiber cloth in this embodiment is exactly the same as that in Example 6, and the mixture ratio is also the same. The difference is that the content of SiO2 in the selected quartz sand accounts for 99.2 wt% of the total quartz sand, the content of Al2O3 accounts for 0.51 wt% of the total quartz sand, and the rest are impurities.
[0051] Comparative Example 7 The method for preparing quartz fiber cloth in this embodiment is exactly the same as that in Example 6, and the mixture ratio is also the same. The difference is that the content of SiO2 in the selected quartz sand accounts for 99.2 wt% of the total quartz sand, the content of Al2O3 accounts for 0.69 wt% of the total quartz sand, and the rest are impurities.
[0052] Comparative Example 8 The method for preparing quartz fiber cloth in this embodiment is exactly the same as that in Example 6, and the mixture ratio is also the same. The difference is that the content of SiO2 in the selected quartz sand accounts for 99.2 wt% of the total quartz sand, the content of Al2O3 accounts for 0.73 wt% of the total quartz sand, and the rest are impurities.
[0053] Comparative Example 9 In this embodiment, a conventional quartz fiber preparation process is adopted, namely, the direct melting method is used to obtain quartz fibers with a SiO2 content of more than 99wt%, and the diameter is controlled at 5~8μm. The quartz fibers are used to weave fabrics with a warp density of 59±2 ends / 25mm and a weft density of 46±2 ends / 25mm.
[0054] Table 3 compares the quartz sand composition and SiO2 content of the final quartz fiber cloth in Examples 6-9 and Comparative Examples 5-9. Comparative Example 5 99.2 0.15 0.65 98.83 Example 6 99.2 0.2 0.6 99.19 Example 7 99.2 0.33 0.47 99.25 Example 8 99.2 0.4 0.4 99.27 Example 9 99.2 0.43 0.37 99.12 Comparative Example 6 99.2 0.51 0.29 98.88 Comparative Example 7 99.2 0.69 0.11 98.81 Comparative Example 8 99.2 0.73 0.07 97.76 Comparative Example 9 / / / 99.31 As can be seen from the table above, in Examples 6-9, when the content of alkaline flux accounts for approximately 18 wt% of the total mixture, and the Al2O3 content is between 0.2% and 0.43%, the final SiO2 content in the quartz fiber cloth reaches over 99 wt%. Furthermore, in Examples 7 and 8, the SiO2 content in the quartz fiber is higher than 99.2%, exceeding the SiO2 content in the raw material quartz sand, indicating a high impurity removal rate. The SiO2 content in Comparative Examples 5, 6, and 7 also reaches 98 wt%.
[0055] The quartz fiber cloths prepared in Examples 6-9 and Comparative Examples 5-8 were subjected to strength tests, and the dielectric loss of the laminates (reinforced PTFE) made from the quartz fiber cloths was tested. The data are shown in Table 4 below. Comparative Example 5 112 warp yarns, 81 weft yarns 0.0015 0.0026 Example 6 121 warp yarns and 90 weft yarns 0.0006 0.0008 Example 7 120 warp yarns and 92 weft yarns 0.0004 0.0006 Example 8 124 warp yarns and 93 weft yarns 0.0005 0.0007 Example 9 Warp 125, weft 92 0.0007 0.0012 Comparative Example 6 Warp 125, weft 93 0.0018 0.0025 Comparative Example 7 119 warp yarns and 87 weft yarns 0.0017 0.0036 Comparative Example 8 Warp 103, weft 82 0.0029 0.0043 Comparative Example 9 (Direct Melting Method) 129 warp yarns and 97 weft yarns 0.0004 0.0005 As can be seen from Table 4 above, the quartz fiber cloths of Examples 6-9 and Comparative Example 6 have excellent tensile breaking strength data. This is because, under the mutual restraint of metal ions in the alkaline flux, as the Al2O3 content increases, it can enter the high silicon phase, increasing the connection degree and strength of the three-dimensional network of SiO2 skeleton, so that the overall strength data shows a gradual upward trend.
[0056] The 2GHz and 10GHz test data of Examples 6-8 are all below 0.0010, indicating excellent dielectric properties. Among them, Example 7 has the best dielectric properties. Although its strength data is slightly lower than that of Example 8, this slight difference in strength can be ignored when applied to low-dielectric quartz fiber cloth. The dielectric properties of Example 7 are basically the same as those of Comparative Example 9, which uses quartz fiber monofilaments prepared by direct melting and then weaving them into quartz fiber cloth. However, since Example 7 uses a multi-bundle filament production process and does not require high-temperature melting, it can be concluded without doubt that its cost is much lower than that of Comparative Example 9. Therefore, Example 7 is the best example.
[0057] Although the overall strength data of Comparative Example 6 is slightly better than that of Examples 6-9, its dielectric loss tangent test data at 2GHz and 10GHz are 0.0018 and 0.0025, respectively, which are several times higher than those of Examples 6-8. This may be because the high Al2O3 content inhibits phase separation, preventing the formation of an interpenetrating and continuous microstructure of high silicon phase and impurity phase. As a result, impurities cannot be fully dissolved and leached out during subsequent acid washing, and the residual impurities cause a sharp increase in dielectric loss.
Claims
1. A method for preparing low-energy-consumption, low-cost quartz fiber, characterized in that, The preparation method includes: In the drawing process, quartz sand with added alkaline flux is melted, and the melting temperature of the mixture is controlled below 1650℃ using alkaline flux to obtain molten quartz precursor; then the molten quartz precursor is drawn into quartz precursor fibers through an alloy porous stencil. The pickling process removes impurity phases from the quartz precursor fibers. In the sintering process, the acid-washed quartz precursor fibers are sintered to obtain quartz fibers with a SiO2 content of over 99%. The quartz sand contains SiO2 and Al2O3, with SiO2 accounting for more than 99 wt% of the total quartz sand and Al2O3 accounting for 0.2-0.43 wt% of the total quartz sand; and the content of alkaline flux in the mixture of quartz sand and alkaline flux is 15-25 wt%.
2. The method for preparing low-energy-consumption, low-cost quartz fiber according to claim 1, characterized in that: The content of Al2O3 in the total amount of quartz sand is controlled at 0.33~0.4wt%; and the content of alkaline flux in the mixture of quartz sand and alkaline flux is 18~24wt%.
3. The method for preparing low-energy-consumption, low-cost quartz fiber according to claim 1, characterized in that: The alkaline flux is sodium carbonate.
4. The method for preparing low-energy-consumption, low-cost quartz fiber according to claim 1, characterized in that: In the pickling process, the pickling solution used for the quartz precursor fibers is hydrochloric acid or sulfuric acid.
5. The method for preparing low-energy-consumption, low-cost quartz fiber according to claim 1, characterized in that: Before the pickling process, the quartz precursor fibers are woven.
Citation Information
Patent Citations
A quartz glass fiber cloth and a preparation method thereof
CN120818934B
Composition for preparing high-silica glass fiber, high-silica glass fiber and preparation method of high-silica glass fiber
CN116253520A
BY7886C1
